Psychological Conflict Seen through Victor Frankenstein: A Psychoanalytic Theory - Cintania Dharma Brillianta; Rafika Zahra; Novia Diah Lestari (ITScience (Information Technology and Science), 2026)
The study aims to analyze the personality structure of the id, ego, and superego as seen through the psychological conflict of Victor Frankenstein, using Sigmund Freud's psychoanalytic theory. This study uses a descriptive-qualitative method. The data analyzed consists of verbal data, such as words, phrases, and sentences in dialogue, as well as visual data in the form of scenes depicting the main character, namely Victor Frankenstein, actions, or expressions in the film Frankenstein (2025). This study shows that Victor Frankenstein's psychological conflict derives from the conflict between the id, ego, and superego in his personality structure. The id is the most dominant personality structure in Victor Frankenstein. The dominance of the id causes Victor to ignore the consequences of his actions, and then fear and regret arise, which cause psychological suffering. Thus, Victor's psychological conflict can be interpreted as a failure to balance his desires (id), rational considerations (ego), and moral responsibility within himself (superego).